Low vitamin D level increases women’s breast cancer risks, Sulaimaniyah, Iraq: A case-control study: Correlation between vitamin D level and breast cancer - Abdulqadir, Mardin Othman; Kamal, Niaz Mustafa; Rahman, Heshu Sulaiman (Cellular and Molecular Biology, 2023)
Vitamin D (Vit D) is essential in maintaining calcium homeostasis and other body processes. It has been widely studied how Vit D affects cell cycle pathways and how it affects the development and prevention of breast cancer (BC). This study aimed to determine Vit D insufficiency linkage to the development of BC. In this case-control study, 130 women (65 BC patients and 65 healthy controls) aged 20–60 years who visited Shar Hospital Breast Center in Sulaimaniyah, Iraq, from December 2021 to May 2022 were included. Patients were selected after their diagnosis had been verified by breast ultrasound, mammography, and core biopsy. The ELISA test was used to measure the concentrations of serum Vit D and expressed in ng/ml. The results showed that the BC patients had considerably lower serum Vit D levels that were <20 ng/L in 66.1% (n=43) and 43.1% (n=28) in healthy controls. Compared to the control group (20.2±8.7), the mean Vit D level in BC patients was lower (17.8±8.6). A logistic regression test revealed a substantial increase in the risk of BC for low-level Vit D concentrations below 20 ng/L (OR 2.59, 95% CI 1.24-5.38; P=0.009). Vit D is still a significant risk factor for boosting the likelihood of developing BC after age and body mass index (BMI) adjustments (AOR 2.30, 95% CI 1.1-4.86; p=0.03 and AOR 3.67, 95% CI 1.55-8.7; p=0.002 for BC patients and controls, respectively). According to the outcomes of our investigations, we concluded that Vit D insufficiency raises the risk of BC among women in Sulaimaniyah, Iraq.